Thermodynamic and structural investigation of the specific SDS binding of humicola insolens cutinase. (16th June 2014) - Kold, David; Dauter, Zbigniew; Laustsen, Anne K.; Brzozowski, Andrzej M.; Turkenburg, Johan P.; Nielsen, Anders D.; Koldsø, Heidi; Petersen, Evamaria; Schiøtt, Birgit; De Maria, Leonardo; Wilson, Keith S.; Svendsen, Allan; et al.
Abstract: The interaction of lipolytic enzymes with anionic surfactants is of great interest with respect to industrially produced detergents. Here, we report the interaction of cutinase from the thermophilic fungus Humicola insolens with the anionic surfactant SDS, and show the enzyme specifically binds a single SDS molecule under nondenaturing concentrations. Protein interaction with SDS was investigated by NMR, ITC and molecular dynamics simulations. The NMR resonances of the protein were assigned, with large stretches of the protein molecule not showing any detectable resonances. SDS is shown to specifically interact with the loops surrounding the catalytic triad with medium affinity ( K a ≈ 10 5 M −1 ). The mode of binding is closely similar to that seen previously for binding of amphiphilic molecules and substrate analogues to cutinases, and hence SDS acts as a substrate mimic. In addition, the structure of the enzyme has been solved by X‐ray crystallography in its apo form and after cocrystallization with diethyl p ‐nitrophenyl phosphate (DNPP) leading to a complex with monoethylphosphate (MEP) esterified to the catalytically active serine. The enzyme has the same fold as reported for other cutinases but, unexpectedly, esterification of the active site serine is accompanied by the ethylation of the active site histidine which flips out from its usual position in the triad. Abstract : Interactive Figure 3 ;Interactive Figure 1 | PDB Code(s):4OYY ;4OYL